Medkulturni dialog in evropska območja družbenega in kulturnega stika - Bufon, Milan (Annales. Series historia et sociologia, 2008)
The European continent, the motherland of nationalism, and the part of the world where political borders and different territorial and cultural identities are mostly inter-related, is now facing new challenges regarding how best to represent its numerous interests within one system. With the increase of international integration European countries began to devote greater attention to the development problems of their border areas that had to be helped to undertake certain functions in the international integration process. The fostering of a more balanced regional development also resulted in a strengthening of regional characteristics, which the new model could no longer ignore. Regional characteristics in turn have always been preserved in Europe by persistent historical and cultural elements of ethnic and linguistic variety. Therefore it is not surprising that the process of European integration based on the new regional development model was accompanied by a parallel process of ethnic or regional awakening of minorities and other local communities. The key question for contemporary European political geography is, then, how the process summarised under the twin labels of social convergence and divergence will effect on the one hand the persistent maintenance of regional identities and on the other hand the corresponding potentials for inter-cultural
Keywords: Europe; Evropa; integracijski procesi; kulturni stiki; medkulturni dialog; regije